Calibration of Video-Oculographical Eye-Tracking System - Ramanauskas, N. (Elektronika ir Elektrotechnika, 2006)
Video-oculography (VOG) is the most suitable eye tracking method in Human Computer Interaction. The precise mapping from image co-ordinates to computer monitor screen co-ordinates in real time is necessary for efficient computer control. During this study, the calibrations techniques were investigated. It was noticed that, there is no significant difference between a mapping with developed model, describing eye image formation process in the sensor, and with polynomial calibration. Polynomial calibration model do not allow a free head motion and requires frequent recalibration. A model based mapping is tolerant to head motions. An improved model could take an advantage over polynomial mapping. Ill. 7, bibl. 8 (in English, summaries in English, Russian, Lithuanian).